Method for manufacturing three-dimensional nanostructures with large aspect ratios
The ink containing metal nanoparticles is deposited on the substrate by an oscillating ejector, and a three-dimensional nanostructure is formed using volatile solvents, which solves the problem of difficulty in manufacturing high aspect ratio nanostructures in the prior art, and achieves rapid, simple and smooth surface manufacturing of nanostructures.
Patent Information
- Application Number
- CN202380064133.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-13
- Filing Date
- 2023-07-13
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to effectively manufacture three-dimensional nanostructures with an aspect ratio greater than 1, and the resulting structural surface is rough, the manufacturing time is long or the process is complicated.
By oscillating between a low position of the contact substrate and a high position without contact, ink containing metal nanoparticles and volatile solvent is deposited, and a three-dimensional nanostructure is formed by volatilizing the solvent.
A rapid and simple fabrication of nanostructured columns with an aspect ratio greater than 1 is achieved, with smooth surfaces or layered without the need for conductive substrates.
Smart Images

Figure CN119836330A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fabrication of three-dimensional nanostructures, and in particular to the fabrication of nanostructures, such as nanostructure pillars, having a large aspect ratio greater than 1. In particular, these pillars may have the shape of a cylinder with a substantially constant diameter in an upward direction, or a conical pin shape with a decreasing diameter in an upward direction.
[0002] The three-dimensional nanostructures may be used in the fields of microelectronics, optoelectronics, energy conversion, nanodevice fabrication or nanosensor fabrication, in particular for incorporation into screens, processors (and in particular quantum processors) or in vitro diagnostic devices. Background Art
[0003] Various techniques exist for producing three-dimensional nanostructures with aspect ratios greater than 1.
[0004] The aspect ratio of a structure is understood here to be the ratio of the two dimensions of the structure. In particular, when the structure is extended in a direction of extension and forms, for example, a column or a pin, the aspect ratio is the ratio of the length of the structure in the direction of extension to the width of the structure in a direction transverse or perpendicular to this direction of extension. The greater the ratio, the greater the stretching of the structure in the direction of extension and, for a column, the smaller its diameter is relative to its height.
[0005] Three-dimensional nanostructures with aspect ratios greater than 10:1 can be fabricated by direct 3D printing using silver Newtonian inks with fast drying properties. See Lee et al. ACS Appl. Mater. Interfaces 2017, 9, 22, 18918–18924 for this topic. However, the structures produced by this technique have very bumpy surfaces.
[0006] There are also techniques based on photosensitive solution polymerization. They require the use of a mixture of a metal colloidal suspension and a photosensitive monomer (a monomer that polymerizes during fabrication). However, the resulting structures are porous and have poor electrical conductivity. These techniques can also be used to produce molds for nanoimprint lithography (NIL). Therefore, the manufacturing process is more expensive because a mold is required for each size and each nanostructure configuration.
[0007] There are also technologies based on applying an electric field between a conductive substrate and a conductive suspension, such as electrodeposition techniques or redox electrohydrodynamic techniques, such as the techniques described by Reiser et al. (Nature Communications, Vol. 10, 1, 2019). It requires the use of conductive inks and carriers, especially due to electroplating (galvanisation) limitations. The manufacturing speed is slow because it is limited by the kinetics of the chemical reaction occurring at the tip of the capillary or the tip of the AFM used. In addition, in the case of electrohydrodynamic techniques, these techniques require dropwise (and therefore discontinuous) deposition, and the satellite droplets produced can cause undesirable surface irregularities.
[0008] Finally, there are technologies based on application by direct printing, in which the deposition of the metallic ink is monitored by a camera.
[0009] Therefore, there is a need for a method for fabricating three-dimensional nanostructures with improved surface conditions, thereby achieving shorter or simpler fabrication times by eliminating the need for a system that uses a camera to monitor deposition. Summary of the invention
[0010] The object of the present invention is to provide a method for manufacturing three-dimensional nanostructures, and in particular nanostructures with an aspect ratio greater than 1, so that nanostructures with smoother or layered surfaces can be produced at a faster speed than the prior art, and the method does not require a conductive substrate as in some prior art.
[0011] In the context of the present invention, this object is achieved by a production method according to the claims, in other words, the method comprises the following steps:
[0012] - oscillating the injector (100) between a low position in contact with the substrate (20) and a high position out of contact with the substrate (20), the injector (100) comprising an injection hole (108) having a diameter greater than 0.1 μm;
[0013] - during the period when the ejection hole (108) of the ejector (100) is in contact with the substrate (20), an ink is deposited on the substrate (20) by the ejector, the ink comprising, in volume % relative to the total volume of the ink:
[0014] - less than 15% of nanoparticles selected from metal nanoparticles, metal oxide nanoparticles, graphene oxide nanoparticles, quantum dots or combinations thereof;
[0015] -0.5% to 5% dispersant,
[0016] - at least 80% of a solvent capable of dispersing the metal nanoparticles to form the ink to be jetted and having sufficient volatility to allow the ink to solidify once deposited; and
[0017] - withdrawing the ejector (100) from the substrate (20) in a direction substantially perpendicular to the substrate at a speed less than or equal to 10 μm / s while maintaining a flow of ink exiting from the ejector.
[0018] The expression "substantially perpendicular" indicates that a direction forms an angle of 90°±10° with a substrate as its base.
[0019] The method steps consist of withdrawing the ejector from the substrate in a direction not parallel to the substrate while maintaining a flow of ink exiting the ejector, so that nanostructure pillars with aspect ratios greater than 1 can be produced, such as pillars with a diameter of 1 μm and a length of 30 μm. These pillars also advantageously have low surface roughness. In addition, the method speeds up the production of pillars, requiring only a few seconds per pillar, and can be performed with any substrate without electroplating restrictions.
[0020] The method is advantageously further characterized by the following features alone or in combination:
[0021] - the ink comprises from 0.05% to 15% by volume, advantageously from 0.2% to 10% by volume, more advantageously from 4 to 8% by volume of nanoparticles relative to the total volume of the ink;
[0022] The diameter of the injection hole (108) is 0.1 μm to 50 μm, advantageously 0.5 μm to 30 μm;
[0023] - the volatile solvent comprises a solvent selected from water, alcohols, glycols, glycol ethers, and mixtures thereof;
[0024] - the ink comprises 80% to 99.45% by volume of the solvent relative to the total volume of the ink;
[0025] The volatile solvent further comprises a second solvent which is glycerol, advantageously such that the ink comprises a glycerol content ranging from 0% to 25% by volume relative to the total volume of the ink.
[0026] - the metal of the metal nanoparticles is selected from silver, copper, gold, platinum, nickel, aluminum, cobalt, combinations thereof or alloys thereof;
[0027] - The metal oxide of the metal oxide nanoparticles is selected from ZnO, TiO2 or V2O5;
[0028] -The ink further comprises a dispersant, which is advantageously selected from polyvinyl pyrrolidone (PVP), gum arabic, polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyallylamine (PAAm), sodium polystyrene sulfonate (PSS), 3-(aminopropyl)trimethylsilane (APS), fatty acids, cetyltrimethylammonium bromide (CTAB), tetraoctylammonium bromide (TOAB), sodium citrate, laurylamine, dodecanethiol, mercapto-polyethylene glycol, mercapto-polypropylene glycol, or a combination thereof.
[0029] - during the step of withdrawing the ejector from the substrate, the ejector is withdrawn at a speed of 1 μm / s to 10 μm / s;
[0030] - the method comprises a step of breaking between the three-dimensional nanostructure formed and the ink to be deposited, advantageously by withdrawing the ejector (100) from the substrate (20) at a speed greater than 10 μm / s;
[0031] The method comprises performing at least one cycle of the following steps in order to form at least one second three-dimensional nanostructure:
[0032] moving the injector relative to the substrate (20) in a direction (x, y) parallel to the substrate, and
[0033] Perform the method steps as described above.
[0034] - The method comprises a step of curing the substrate containing the formed nanostructures.
[0035] The present invention also relates to a product comprising the three-dimensional nanostructure obtained by the method described above.
[0036] The product is advantageously further characterized in that the length of the nanostructures is at least 10 times greater than the width of the nanostructures.
[0037] In another alternative, the product is advantageously further characterized in that the nanostructures have a diameter that decreases in the height direction. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Other features and advantages of the present invention will appear from the following description, which is given for illustration only and is not to be construed as limiting and should be read with reference to the accompanying drawings, in which:
[0039] Figure 1 is a schematic diagram of the formation of a column;
[0040] Figure 2 is a schematic diagram of a system for manufacturing a three-dimensional nanostructure according to one of the embodiments of the present invention;
[0041] Figure 3an image representing the shape of a column obtainable by the method according to the invention;
[0042] Figure 4 An image presenting the shape of the pillar obtained in test 3 (4A), test 4 (4B) or the shape of the flattened dome obtained according to test 8 (4C);
[0043] Figure 5 An image presenting the results after implementing Comparative Example 1;
[0044] Figure 6 Images showing the shapes of the pillars obtained in Example 6 (6A: D=5 μm, 6B: D=10 μm);
[0045] Figure 7 Presents images of the column obtained in Experiment 33;
[0046] Figure 8 Two images presenting the results after implementing Comparative Example 2;
[0047] Fig. 9 Presents images of the column obtained in Experiment 35;
[0048] Fig.10 : 10A is a graphical representation of the maximum withdrawal velocity (Ve, in μm / s) of the reporting pipette as a function of the pipette diameter, wherein the pipette is used for a metal particle volume concentration of 5.8% in the ink, and 10B is a graphical representation of the maximum withdrawal velocity (Ve, in μm / s; the pipette has a diameter of 5±1 μm) of the reporting pipette as a function of the metal particle volume concentration in the ink.
[0049] Fig.11 Images of the columns obtained in experiment 37 are presented.
[0050] Fig.12 Images of the columns obtained in Example 9 are presented. DETAILED DESCRIPTION
[0051] Application WO2020 / 128310 describes a system capable of controlled deposition of ink on any substrate. The system described in this application is capable of depositing ink having a form defined by a length greater than or equal to 1 μm. The system comprises a mechanical resonator attached to an ejector.
[0052] It has now been found that under certain conditions it is possible to deposit an ink and stretch it in an extension direction to form nanostructures such as pillars or pins.
[0053] To carry out this operation, the method described in application WO2020 / 128310 includes a step of withdrawing the ejector from the substrate in a direction non-parallel to the substrate, in particular substantially perpendicular to the substrate, at a speed less than or equal to 10 μm / s, and the ink to be deposited comprises metal nanoparticles and / or metal oxide nanoparticles and / or graphene oxide particles and a sufficiently volatile solvent.
[0054] In the present invention, the term "stretching" means that the deposition is continuous, as opposed to dropwise deposition, for example.
[0055] The three-dimensional nanostructure is formed by evaporating the solvent present in the ink at the outlet of the jet hole. Figure 1 As shown:
[0056] - the substrate and the ejection orifice of the ejector are brought close together. When in contact, a liquid meniscus of the ink contained in the ejector appears between the outlet of the ejection orifice and the substrate (1A);
[0057] - the ejection hole of the ejector and the substrate are withdrawn from each other at a speed less than or equal to 10 μm / s. The inventors believe that the evaporation of the solvent causes the nanoparticles to aggregate and / or locally accumulate at the liquid-gas interface of the meniscus, forming a solid phase consisting of dense agglomerates of nanoparticles (1B and 1C);
[0058] The ejection hole of the ejector and the substrate are withdrawn from each other at a speed greater than 10 μm / s, so that the ejection hole of the ejector is separated from the formed three-dimensional nanostructure (1D).
[0059] The ink used comprises metal nanoparticles or metal oxide nanoparticles or graphene nanoparticles or optionally quantum dots, also referred to below as nanoparticles, and a volatile solvent.
[0060] Advantageously, the ink comprises from 0.05% to 15% by volume of nanoparticles, advantageously from 0.2% to 10% by volume, more advantageously from 4 to 8% by volume.
[0061] The nanoparticles advantageously have an average particle size D50 between 1 nm and 300 nm, advantageously between 30 nm and 200 nm. The particle size can be determined by high resolution scanning electron microscopy (HRSEM) or by light transmission analysis (such as using ) instrument to determine.
[0062] The nanoparticles are advantageously conductive or semiconductive nanoparticles. Advantageously, they are metallic nanoparticles and the metal is selected from silver, copper, gold, platinum, nickel, aluminum, cobalt, zinc, indium, palladium, combinations thereof or alloys thereof. In particular, the nanoparticles are metallic nanoparticles and the metal is selected from silver, copper, gold, platinum, nickel, aluminum, cobalt, combinations thereof or alloys thereof.
[0063] The metal oxide of the metal oxide nanoparticles is advantageously selected from ZnO, TiO2, ITO (indium tin oxide), or V2O5.
[0064] The quantum dots may advantageously be as described, for example, in documents EP2820108, US2014353579 or WO2023274486.
[0065] The ink advantageously also contains a dispersant; in other words, an additive which promotes the dispersion of the metal particles in the ink and which in particular stabilises the ink.
[0066] Advantageously, the ink comprises from 0.5% to 5% by volume, advantageously from 1% to 2% by volume, of dispersant relative to the total volume of the ink.
[0067] The dispersant is advantageously selected from polyvinyl pyrrolidone (PVP), gum arabic, polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyallylamine (PAAm), sodium polystyrene sulfonate (PSS), 3-(aminopropyl)trimethylsilane (APS), fatty acids, cetyltrimethylammonium bromide (CTAB), tetraoctylammonium bromide (TOAB), sodium citrate, laurylamine, dodecanethiol, mercapto-polyethylene glycol, mercapto-polypropylene glycol, or a combination thereof.
[0068] The dispersant may be a polymer having a number average molecular weight Mw of 5000 g / mol to 2,000,000 g / mol. The dispersant is preferably PVP. The molecular weight Mw of PVP is advantageously at least 8000 g / mol, more advantageously 10,000 g / mol to 1,600,000 g / mol, and even more advantageously 10,000 g / mol to 200,000 g / mol.
[0069] When the nanoparticles are silver or copper nanoparticles, the dispersant is advantageously selected from polyvinyl pyrrolidone (PVP), gum arabic, polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyallylamine (PAAm), sodium polystyrene sulfonate (PSS), 3-(aminopropyl)trimethylsilane (APS), fatty acids, cetyltrimethylammonium bromide (CTAB), tetraoctylammonium bromide (TOAB), sodium citrate, laurylamine, or a combination thereof.
[0070] When nanoparticles are gold nanoparticles, dispersants are advantageously selected from mercapto-polyethylene glycol, mercapto-polypropylene glycol, dodecanethiol, sodium citrate, polyvinyl pyrrolidone (PVP) or a combination thereof. Dispersants are preferably mercapto-polyethylene glycol. The molecular weight Mw of mercapto-polyethylene glycol is advantageously at least 100 g / mol, more advantageously 400 g / mol to 2000 g / mol.
[0071] The solvent is firstly a solvent that disperses the nanoparticles without significant agglomeration in the ink. The ink is usually a commercial ink, and the solvent used is a solvent that can already disperse the nanoparticles well. In some cases, a miscible solvent is added to these commercial inks so that its volatility can be improved.
[0072] When the metal particles are silver or copper, examples of solvents which enable good dispersion thereof and which are suitable for the method according to the invention are in particular alcohols, glycols, glycol ethers and mixtures thereof. Of course, mixtures between miscible solvents can be chosen.
[0073] When the metal particles are gold, examples of solvents which enable good dispersion thereof and which are suitable for the method according to the invention are in particular water, alcohols, toluene and mixtures thereof. Of course, mixtures between miscible solvents may be chosen.
[0074] In addition to the ability to disperse the nanoparticles, the solvent must be volatile enough to form a solid phase. In fact, it is hoped that once contact is made between the ejection orifice of the ejector and the substrate, the solvent will evaporate quickly enough to allow local aggregation / accumulation of the nanoparticles while limiting or even avoiding the spread of the ink on the substrate.
[0075] On the other hand, in order to avoid any clogging of the outlet of the injection hole of the injector, the solvent must not evaporate too quickly.
[0076] Thus, the solvent or solvent mixture is advantageously suitable for enabling the formation of a solid phase while, on the one hand, avoiding the formation of clogging or break-off of the deposit and, on the other hand, avoiding or limiting the spreading of the ink on the substrate.
[0077] Of course, the evaporation rate of the solvent depends on the volatility of the solvent, which itself depends on the operating conditions (temperature, pressure, ambient humidity, substrate and jet orifice withdrawal speed and jet orifice diameter) and also on the volume fraction of nanoparticles in the ink.
[0078] Thus, depending on the operating conditions, the ink will contain one solvent or a plurality of solvents, in which case the solvents are miscible with each other.
[0079] In particular, a second solvent of lower volatility may be added to ensure sufficient processing time between the formation of the two structures.
[0080] Without wishing to be limited thereto, the inventors believe that the characteristic time τ for solvent evaporation corresponds to the following formula
[0081] [Mathematical formula 2]
[0082]
[0083] Wherein, D represents the diameter of the injection hole (108),
[0084] P vap It indicates the saturated vapor pressure of the solvent or solvent mixture at the printing temperature at the general ambient temperature.
[0085] ρ sol Indicates the density of the solvent or solvent mixture at printing temperature at normal ambient temperature.
[0086] x v NPs represents the volume fraction of nanoparticles.
[0087] Alternatively, and without wishing to be bound by theory, based on the work of Davis and Ray (J. Chem. Phys. 67, 414 (1977)), the inventors assume that the evaporation rate of the solvent in the ink droplet follows the following equation:
[0088] [Mathematical formula 3]
[0089]
[0090] in,
[0091] X NP represents the volume fraction of nanoparticles in the ink,
[0092] a represents the radius of the droplet (unit: m),
[0093] D 12 represents the diffusion coefficient of the solvent (1) in the gas (2) (unit: m 2 .s -1 ),
[0094] p vap represents the saturated vapor pressure of the solvent at temperature T (unit: Pa),
[0095] M1 represents the molar mass of the solvent (unit: kg.mol -1 )
[0096] ρ liq Indicates the density of the ink solvent at temperature T (unit: kg.m -3 )
[0097] R represents the universal ideal gas constant (unit: JK -1 .mol -1 )
[0098] T represents temperature (unit: K).
[0099] The gas (2) is typically air.
[0100] After integration, the characteristic time τ for solvent evaporation is derived to be proportional to:
[0101] [Formula 4]
[0102]
[0103] in,
[0104] x NP represents the volume fraction of nanoparticles in the ink,
[0105] r represents the radius of the injection hole (108) (unit: m),
[0106] D 12 represents the diffusion coefficient of the solvent (1) in the gas (2) (unit: m 2 .s -1 ),
[0107] p vap represents the saturated vapor pressure of the solvent at temperature T (unit: Pa),
[0108] M1 represents the molar mass of the solvent (unit: kg.mol -1 )
[0109] ρ liq Indicates the density of the ink solvent at temperature T (unit: kg.m -3 )
[0110] R represents the universal ideal gas constant (unit: JK -1 .mol -1 )
[0111] T represents temperature (unit: K).
[0112] The gas (2) is typically air.
[0113] In the case of a solvent mixture, p vap , liq , and D 12 The value of is of course an average value, weighted as a function of the volume fraction of each solvent.
[0114] These relationships have been verified by experimental measurements, which appear to indicate that the proportionality coefficient is substantially equal to 1.
[0115] Advantageously, the conditions of the diameter of the injection hole, the saturated vapor pressure of the solvent or the solvent mixture, the density of the solvent or the solvent mixture, and the volume fraction of the nanoparticles make the characteristic time τ of solvent evaporation vary between 0.1s and 1000s, particularly between 0.1s and 300s, advantageously between 1s and 30s, and more advantageously between 2s and 10s. Preferably, the conditions of the radius of the injection hole, the saturated vapor pressure of the solvent or the solvent mixture, the density of the solvent or the solvent mixture, and the volume fraction of the nanoparticles make the characteristic time τ of solvent evaporation determined according to equation 4 advantageously vary between 10s and 300s, particularly between 30s and 300s.
[0116] It is observed that according to the two equations Math 2 and Math 4, when the volume fraction of nanoparticles in the ink increases, the volatility of the solvent must decrease.
[0117] It was also observed that when the solvent had a lower evaporation rate, it was necessary to reduce the withdrawal speed.
[0118] Advantageously, the volume fraction of nanoparticles in the ink, the radius of the injection hole (108) and the solvent are selected (temperature and gas are usually fixed to 300K and air, respectively) so that the characteristic time τ of solvent evaporation determined according to equation (4) advantageously varies between 10s and 300s, in particular between 30s and 300s.
[0119] Advantageously, the volatile solvent comprises a solvent selected from water, alcohols, glycols, glycol ethers and mixtures thereof. Of course, in the case of a solvent mixture, the solvents must be miscible and the mixture continuous in order to ensure that it functions to disperse the nanoparticles.
[0120] Specifically, examples of the alcohol include methanol, ethanol, isopropanol, 1-propanol, benzyl alcohol, and terpineol.
[0121] Specifically, examples of the glycol include ethylene glycol, propylene glycol, butylene glycol, pentylene glycol, hexylene glycol, diethylene glycol, and triethylene glycol.
[0122] Specifically, examples of glycol ethers include:
[0123] -ethylene glycol ether, propylene glycol ether;
[0124] -propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, propylene glycol mono-t-butyl ether, propylene glycol monophenyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, propylene glycol mono-t-butyl ether, tripropylene glycol monoethyl ether, tripropylene glycol monopropyl ether and tripropylene glycol monobutyl ether;
[0125] -ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monophenyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, diethylene glycol mono-t-butyl ether, triethylene glycol monopropyl ether and triethylene glycol monobutyl ether.
[0126] Specifically, the solvent is selected from water, ethanol, ethylene glycol (EG), diethylene glycol methyl ether (DGME), diethylene glycol ethyl ether (DGEE), diethylene glycol butyl ether (DGBE), triethylene glycol methyl ether (TGME), propylene glycol ethyl ether (PGME), tripropylene glycol methyl ether (TPME) and mixtures thereof.
[0127] Advantageously, the ink comprises from 80% to 99.45% by volume of said solvent relative to the total volume of the ink. This content corresponds to the content of the first solvent and the second solvent, when the second solvent is present, as defined below.
[0128] This solvent, also referred to as the first solvent, can be used alone. Alternatively, it can be mixed with a less volatile solvent, referred to as the second solvent.
[0129] As indicated, the ink may comprise a second solvent having a much lower volatility than the first solvent. This second solvent is advantageously hygroscopic. Thus, advantageously, the volatile solvent comprises a second solvent selected from glycerol, in an amount advantageously such that the ink comprises 0% to 25% by volume of glycerol relative to the total volume of the ink.
[0130] The purpose of the second solvent is to prevent the spray hole from drying out too quickly and clogging. Depending on the humidity level of the air and the volume fraction of the second solvent, the spray hole can remain inactive in the air for 1 minute to 30 minutes before the formation of nanostructures resumes.
[0131] Thus, for example, nanostructures can be created one after another with a time interval of 30 seconds to 30 minutes between the individual nanostructures, without the jetting orifice becoming clogged between two nanostructures.
[0132] Advantageously, the ink comprises four components, more advantageously consists of four components:
[0133] - nanoparticles as described above, having a volume concentration of 0.05% to 15% by volume, preferably between 4% and 8% by volume;
[0134] - the dispersant as described above, having a volume concentration of 0.5% to 5% by volume, preferably 1% to 2% by volume;
[0135] - a first solvent selected from the group consisting of water, ethanol, ethylene glycol (EG), diethylene glycol methyl ether (DGME), diethylene glycol ethyl ether (DGEE), diethylene glycol butyl ether (DGBE), triethylene glycol methyl ether (TGME), propylene glycol ethyl ether (PGME), tripropylene glycol methyl ether (TPME) and mixtures thereof;
[0136] - 0 to 25% by volume of glycerol.
[0137] The percentages are expressed in volume relative to the total volume of the ink. When the ink is composed of these four components, it contains 55% to 99.45% by volume of the first solvent.
[0138] System for fabricating three-dimensional nanostructures
[0139] Figure 2 An embodiment of a system 10 for fabricating three-dimensional nanostructures on a substrate 20 is shown.
[0140] In this case, the system 10 comprises all the features of a system for controlling the deposition of ink on a substrate such as presented in application WO 2012 / 078590. This document is incorporated by reference. Reference may be made to this application for more details of known aspects of the implemented technology.
[0141] The system 10 for fabricating a three-dimensional nanostructure on a substrate 20 includes a nano-sized injector 100 .
[0142] The ejector 100 includes a reservoir 102 for storing ink and a non-deformable protrusion 104. The ejector 100 includes an ejection hole 108 for drawing out the ink from the reservoir 102.
[0143] The diameter of the injection hole 108 is 0.1 to 50 micrometers, and advantageously 0.5 to 30 micrometers.
[0144] The system 10 also includes a conveyor or moving device 160 suitable for moving the substrate 20 relative to the injector 100. The movement can be performed in a direction z that is non-parallel to the substrate, as well as in directions x and y that are parallel to the substrate. The moving device 160 can be a piezoelectric scanner for deposition of the substrate 20. In particular, it can be a three-axis piezoelectric scanner with sub-nanometer movement resolution.
[0145] The system 10 further includes a mechanical resonator attached to the ejector 100 .
[0146] The mechanical resonator may be in the form of a diapason, the body of which is screwed onto its base, which rests on a block that moves along three spatial axes via a system of micro-screws.
[0147] The system 10 further comprises a controller or control means 148 of the mechanical resonator. The controller 148 comprises a first PID controller 1 connected to an exciter or excitation means 142 adapted to excite the mechanical resonator.
[0148] The system 10 includes an excitation device 142, which may be a piezoelectric actuator. The actuator is coupled to the mechanical resonator.
[0149] The control device 148 is further connected to a detector or detection device 144 adapted to detect the oscillations of the mechanical resonator in order to read the response of the mechanical resonator to the excitation of the excitation device 142. The system 10 comprises a detector 144 which may be an accelerometer coupled to the mechanical resonator.
[0150] The detector 144 is capable of detecting variations in the oscillations, in particular variations of the oscillation frequency of the ejector of less than 1 Hz, advantageously between 10 mHz and 200 mHz.
[0151] The control device 148 is also connected to a regulator or regulating device 146 suitable for adjusting the contact between the protrusion 104 and the substrate 20 by controlling the oscillation of the mechanical resonator.
[0152] The system 10 comprises a regulator 146 which is a second PID controller 2 and is able to regulate the contact using the conveyor or moving device 160 to which it is connected.
[0153] As regards the excitation of the resonator, it should be noted that the piezoelectric actuator can be powered by an electrical signal, the frequency of which corresponds to its mechanical excitation frequency. The frequency of this electrical signal is adjusted by the first PID controller 1 in order to control the oscillation of the tuning fork, so that the response of the tuning fork detected by the accelerometer is in phase with the signal of the piezoelectric actuator, so that the tuning fork oscillates according to the oscillation of the piezoelectric actuator. The set point of this feedback loop is therefore that the phase shift between the oscillation of the piezoelectric actuator and the oscillation of the tuning fork is zero. The tuning fork is thus in phase with the piezoelectric actuator. The tuning fork is thus excited at its resonant frequency, which depends on its mechanical properties and also on the interaction with its environment.
[0154] The control device 148 is adapted to deposit the aforementioned ink on the substrate 20 via the ejector 100 during the period in which the ejector 100 is in contact with the substrate 20 .
[0155] The control device 148 is connected to the conveyor 160 and is adapted to withdraw the ejector from the substrate 20 in a z-direction that is non-parallel to the substrate while maintaining a flow of ink exiting from the ejector. The z-direction may be a direction perpendicular to the plane of the substrate 20.
[0156] Method for producing three-dimensional nanostructures
[0157] The manufacturing system just described can implement the method for manufacturing a three-dimensional nanostructure according to the present invention.
[0158] One embodiment for carrying out this method is presented below.
[0159] The first step of the method comprises oscillating the injector 100 between a low position in contact with the substrate 20 and a high position out of contact with the substrate 20 .
[0160] Typically, during this step, the ejector oscillates with an amplitude of between 0.5 nm and 100 nm, advantageously between 1 nm and 20 nm.
[0161] For this purpose, the control device 148 can control the excitation device 142 to excite the mechanical resonator, which itself oscillates the ejector 100. Thus, the protrusion 104 oscillates between a low position in which the protrusion 104 is in contact with the substrate 20 and a high position in which the protrusion 104 is not in contact with the substrate 20.
[0162] The resonance of the system consisting of the tuning fork, piezoelectric actuator and accelerometer can be measured to determine the resonant frequency of the tuning fork and its quality factor.
[0163] It is also possible to predefine a phase shift of the setpoint oscillation of the second PID controller 2, this phase shift corresponding to the phase shift caused by a predefined contact between the protrusion and the substrate 20. By way of example, this phase shift may be less than 1 Hz, advantageously 10 to 200 mHz (millihertz).
[0164] The protrusion 104 is brought close to the substrate 20 using the conveyor 160 in such a way that the protrusion 104 oscillates between a low position in which it is in contact with the substrate 20 and a high position in which it is not in contact with the substrate 20. In this particular configuration of the protrusion 104 and the substrate 20, the force applied to the assembly consisting of the tuning fork and the ejector 100 is changed. This changes the resonant frequency and therefore the excitation frequency of the piezoelectric actuator, which is maintained at the resonant frequency of the tuning fork.
[0165] This configuration may be chosen to be defined by a certain change, for example less than 1 Hz, advantageously from 10 to 200 mHz, of the resonant frequency of the assembly formed by the tuning fork and the ejector 100. This change is the phase shift induced above.
[0166] Via the detector 144 , the system 10 is suitable for identifying a specific configuration between the injector and the substrate involving a variation of the oscillation of less than 1 Hz, advantageously from 10 mHz to 200 mHz.
[0167] Using the second PID controller 2 and as a function of the change in oscillation, the configuration can be adjusted so as to form an ink meniscus between the protrusion 104 and the substrate 20. The regulator or second PID controller 2 controls the fine approach between the substrate 20 and the ejector 100 via a feedback loop until the change in the resonant frequency is less than 1 Hz, advantageously from 10 mHz to 200 mHz.
[0168] The second step of the method consists in depositing the aforementioned ink on the substrate 20 by means of the ejector 100 while the ejector 100 is in contact with the substrate 20 .
[0169] When contact is made, a meniscus of the liquid (the aforementioned ink) contained in the pipette appears between the ejection hole 108 and the substrate 20 (see Figure 1 ).
[0170] Contact is maintained by imposing a constraint on the frequency offset of the resonance, which offset is produced by the interaction between the injection orifice 108 and the substrate 20. The "frequency offset" value used is advantageously between 40 mHz and 500 mHz.
[0171] As indicated previously, the amplitude of the oscillations of the tuning fork and thus of the protrusion 104 is fixed between 0.5 nm and 100 nm.
[0172] The ink thus deposited on the substrate forms the basis for the fabricated three-dimensional nanostructures.
[0173] Prior to the subsequent third step, the method may include a step during which contact is maintained without withdrawing from the ejector 100. This step corresponds to the start-up time, allowing the meniscus formed by the nanoparticles to be gathered. Therefore, the more the ink is diluted, the greater the advantage of observing the start-up time. This start-up time advantageously varies from 1 s to 180 s.
[0174] The third step of the method consists in withdrawing the ejector 100 from the substrate 20 in a direction that is non-parallel, advantageously substantially perpendicular to the substrate, while maintaining a flow of ink exiting from the ejector.
[0175] The ink exiting from the ejector during this step is deposited on the previously deposited ink so as to gradually form a three-dimensional nanostructure. The nanostructure thus produced comprises portions extending in a direction that is not parallel, advantageously substantially perpendicular to the substrate.
[0176] As previously indicated, the ejector's withdrawal speed is adjusted so that the exiting ink solidifies fairly quickly, thereby serving as a base for the subsequent exiting ink to be deposited.
[0177] By way of example, during this step, the system may be adjusted so that the ejector is withdrawn at a predetermined speed less than or equal to 10 μm / s, advantageously between 1 μm / s and 10 μm / s.
[0178] Advantageously, once contact is established, the substrate 20 is withdrawn from the protrusion 104 according to one of the following two modes:
[0179] 1) The feedback control loop of the mobile device 160 is kept active via the regulator 146 (PID controller 2):
[0180] The presence of the solid phase generates local irregularities on the substrate, which results in a frequency shift detected by the phase-locked loop. The mobile device 160 responds to this increase in frequency shift by withdrawing the substrate 20 sufficiently to find a set point value for the frequency shift fixed at a value between 40 mHz and 500 mHz. Thus, the creation of the column is initiated. This procedure continues automatically as long as the operator keeps the feedback control loop active and the column is continuously drawn out from the tip of the injection orifice 108. Deactivation of the feedback control loop of the mobile device 160 suspends the creation of the column.
[0181] The column obtained according to this variant advantageously has a smooth appearance ( Figure 3 3A, 3C in ). If the set point value is changed, the column can be given a wavy shape ( Figure 3 3E in ).
[0182] 2) Deactivate the feedback control loop of the mobile device 160 via the regulator 146 (PID controller 2):
[0183] Just after forming the meniscus, the operator waits 1 s to 60 s in contact to initiate the formation of the pillars before manually withdrawing the substrate 20 from the protrusion 104 using the control software. The distance increment has a value of 0.01 μm to 10 μm, providing a withdrawal speed of from 0.01 μm / s to 10 μm / s. Advantageously, an activation time of 0.1 s to 60 s may be provided between each distance increment.
[0184] The columns obtained according to this variant advantageously have a layered appearance ( Figure 3 If the withdrawal speed is changed, the column can be made to have a wavy shape.
[0185] In any case, in order to detach the protrusion 104 from the pillar, in a fourth step, also called a breaking step, the substrate is withdrawn at a speed of at least 10 μm / s. It is known that the faster the withdrawal speed (>500 μm / s), the flatter the top of the pillar will be ( Figure 3 In contrast, too slow a withdrawal speed (<20 μm / s) will cause the top of the column to be tapered, and the slower the withdrawal speed, the longer the cone ( Figure 3 3A, 3B).
[0186] This method allows the manufacture of columns in the order of seconds.
[0187] This method makes it possible to proceed without the use of a camera to monitor and control the deposition. This method makes it possible to overcome the pressure on the ink to be deposited.
[0188] It is thus possible to produce nanostructured pillars with an aspect ratio greater than 1, advantageously between 10:1 and 50:1, such as pillars with a diameter of 1 μm and a length of 30 μm.
[0189] In particular, such a column is obtained using an injector whose injection orifice 108 has a diameter of 0.1 μm to 50 μm, advantageously 0.5 μm to 30 μm, more advantageously 1 μm to 15 μm.
[0190] The shape of the column will depend on the operating conditions. Figure 3 As illustrated, the pillars may be formed into shapes having the following characteristics:
[0191] - a smooth cylinder with a substantially constant diameter terminating in a conical top ( Figure 3 3A in );
[0192] - a layered cylinder, having a substantially constant diameter, terminating in a conical top ( Figure 3 3B in );
[0193] - a smooth cylinder with a substantially constant diameter terminating in a flat top ( Figure 3 3C in the
[0194] - a layered cylinder, having a substantially constant diameter, terminating in a flat top ( Figure 3 3D in );
[0195] - Smooth cylinder with varying diameter and wavy shape ( Figure 3 3E in );
[0196] - cylinder, with alternating smooth and stratified areas ( Figure 3 3F in );
[0197] - a column in the form of a conical pin with a diameter that decreases in the height direction ( Figure 3 3G in the Internet).
[0198] The method advantageously also comprises performing a relative movement of the ejector relative to the substrate (20) in a direction (x, y) parallel to the substrate, so as to deposit ink to form at least one line, according to the method described in WO2020 / 128310.
[0199] The method may be suitable for continuously manufacturing a plurality of nanostructures. For this purpose, the method may further comprise performing at least one cycle of the following steps to form at least one second three-dimensional nanostructure:
[0200] - moving the injector relative to the substrate 20 in a direction (x, y) parallel to the substrate, and
[0201] -Perform the steps of the method as described above.
[0202] The relative movement is ensured by a moving device 160. During the relative movement of the ejector relative to the substrate (20) in a direction (x, y) parallel to the substrate, ink can be deposited to form at least one line according to the method described in WO 2020 / 128310.
[0203] Each time the cycle of steps is performed, new nanostructures are created.
[0204] Once the pillar or pillars have been formed, the method advantageously comprises a curing step. The conditions of this step can be adjusted according to the nature of the metal or oxide of the nanoparticles. For example, pillars made of gold or silver are heated to a temperature of 130° C. to 200° C. for a duration that can vary between 10 minutes and 2 hours. The conditions for pillars made of copper, temperature and duration can be the same, only having to operate in a non-oxidizing atmosphere, for example, under argon, nitrogen or hydrogen. Photonic curing can also be performed, which can be carried out in ambient atmosphere, even for copper pillars.
[0205] Advantageously, all steps of the process are carried out at ambient temperature (18-22° C.) and atmospheric pressure.
[0206] Finally, the invention relates to a product obtained by a method such as that just described, comprising a substrate on which three-dimensional nanostructures are deposited.
[0207] According to an alternative embodiment, the nanostructure is a column as described above. The column advantageously has an aspect ratio greater than 10:1, more advantageously greater than 15:1, and even more advantageously up to 50:1, so that the extension length of the column in the extension direction is at least ten times the width of the nanostructure in a direction perpendicular to the extension direction.
[0208] This extension direction corresponds to a z-direction which is non-parallel to (advantageously substantially perpendicular to) the substrate, in which direction the ejector is withdrawn from the substrate during the method.
[0209] The base diameter of the pillars corresponding to their greatest width is advantageously smaller than 10 μm, more advantageously smaller than 5 μm, even more advantageously smaller than 2 μm, for example 1 μm.
[0210] According to another alternative, this nanostructure is a pin as previously described.
[0211] The controllable parameters are the diameter of the base and the apex of the pin, and the slope angle formed between its vertical wall and the axis perpendicular to the substrate. The diameter of the base advantageously varies between 0.5 μm and 50 μm, more advantageously between 1 and 30 μm. The diameter of the apex advantageously varies between 0.2 μm and 30 μm, more advantageously between 0.5 μm and 10 μm. The slope angle formed between its vertical wall and the axis perpendicular to the substrate advantageously varies between 0.1° and 70°, more advantageously between 10° and 45°.
[0212] This shape is interesting for producing solder bumps in the steps for packaging electronic chips. Tapered pins have a higher mechanical stability than pillars when shear stress is applied to them. This usually occurs during the wafer bonding step, during which the pins deposited on the silicon wafer are compressed vertically by the pressure of the silicon wafer 2. During the compression process, a small movement in the xy of the silicon wafer can dislocate the pillars and impair the proper bonding of the two silicon wafers. Due to their morphology, tapered pins are less affected by this phenomenon.
[0213] Advantageously, in any of the variants described, the substrate is non-conductive.
[0214] The following examples illustrate the invention.
[0215] Characteristic time of evaporation of various solvents
[0216] The equation used was Mathematical Formula 4, with the following parameters:
[0217] x NP Set to 0.06.
[0218] 2a (pipette diameter) = 1.5*10 -5 m
[0219] R=8.3JK -1 .mol -1
[0220] T=300K
[0221] D 12 represents the diffusion coefficient of solvent (1) in air (gas (2)). It has been calculated using the Chapman-Enskog equation:
[0222]
[0223] in:
[0224] N represents Avogadro's number (6.02214076×10 23 mol -1 )
[0225] k represents the Boltzmann constant (1.380649×10 -23 JK -1 )
[0226] T represents temperature, the unit is K (300K)
[0227] M sol Indicates the molar mass of the solvent in kg.mol -1
[0228] M air Indicates the molar mass of air in kg.mol -1 (0.029kg.mol -1 )
[0229] p represents pressure, the unit is Pa (1.01*10 5 Pa)
[0230] σ is the diameter of the effective cross section corresponding to the solvent molecule, in m
[0231] Ω represents the collision integral minus the hard-ball collision value, which is approximately 1
[0232] pvap It represents the saturated vapor pressure of the solvent at 300K.
[0233] ρ liq It represents the density of the ink solvent at a temperature of 300K.
[0234]
[0235]
[0236] The above values of the characteristic time of solvent evaporation were measured on the experimental device described in Examples 1 to 10. The experimental values are in fact consistent with the theoretical values obtained according to equation 4. In particular, in the case of a pipette diameter of 1.5*10 -5 In the case of m, the solvents consisting of TEG alone or glycerol alone are not sufficiently volatile to allow the ink to solidify once deposited.
[0237] Example 1: Silver Nanoparticles – Commercial Ink
[0238] Commercial ink PVnanocell ref(Sycris TM I40DM-106) The composition specified by the supplier includes:
[0239] -Silver nanoparticles (d50 = 70nm, d90 = 152nm, Determination), coated with a layer of polyvinyl pyrrolidone; its concentration is between 38% by weight and 42% by weight by mass, that is, about 5.8% by volume.
[0240] -Solvent DGME,
[0241] The commercial inks were injected into drawn glass capillaries (= pipettes) with the diameter of the tip as indicated in Table 1, taking care that the liquid actually reached the end of the tip of the pipette.
[0242] According to application WO2020 / 128310 Figure 2 In the method described, the pipette is fixed to one of the two forks of the tuning fork and approaches its tip. In the first step, a micrometer cursor (micrometric vernier) is used to mechanically bring the tip of the pipette close to the substrate, which is a silicon wafer in this case, less than 300 μm away. Next, a loop (phase-locked loop (PLL)) that maintains the resonance of the tuning fork and a feedback control loop on the piezoelectric scanner are used to approach the substrate until contact is made, so as to achieve contact between the tip of the pipette and the substrate. Here, the substrate is placed on the piezoelectric scanner, the pipette is therefore fixed, and it is the substrate that approaches the pipette.
[0243] The contact is maintained by imposing a constraint on the frequency shift (FS) of the resonance, which is generated by the interaction between the pipette and the substrate. The value of the frequency shift FS used is 150 mHz (millihertz).
[0244] The oscillation amplitude of the tuning fork (and therefore of the pipette) was fixed at 10 nm.
[0245] When contact is made, a meniscus of the liquid (ink) contained in the pipette appears between the tip of the pipette and the substrate.
[0246] Once contact is established, the substrate is withdrawn from the pipette according to one of two modes:
[0247] 1) The feedback control loop of the piezoelectric scanner remains valid:
[0248] The presence of the solid phase generates a local irregularity on the substrate, which results in a FS detected by the PLL. The piezoelectric scanner can respond to this increase in FS by withdrawing sufficiently from the substrate to return to the set value of FS fixed at 150 mHz. Thus, the creation of the column is initiated. This procedure continues automatically as long as the operator keeps the feedback control loop active and continuously draws the column out of the tip of the pipette. Deactivation of the feedback control loop of the piezoelectric scanner pauses the creation of the column.
[0249] To disengage the pipette from the column, withdraw the pipette at a speed of at least 10 μm / s.
[0250] 2) The feedback control loop of the piezoelectric scanner is disabled:
[0251] Just after the meniscus is formed, the operator waits 1 s to 60 s in contact to initiate the formation of the pillars and then manually withdraws the substrate from the pipette using the control software. The distance increment has a value of 0.01 to 10 μm, providing a withdrawal speed from 0.01 to 10 μm / s.
[0252] Once the correct dimensions are obtained, in order to disengage the pipette from the column, the method is carried out as described in the previous point.
[0253] All steps of the process are carried out at ambient temperature (18-22°C) and atmospheric pressure.
[0254] The results obtained are summarized in the following table:
[0255] [Table 1]
[0256]
[0257] D = pipette diameter (μm)
[0258] Ve=withdrawal speed (μm / s)
[0259] Vr=fracture velocity (μm / s)
[0260] Given the following diagram:
[0261] - Figure 4 4A: Column obtained according to Experiment 3;
[0262] - Figure 4 4B: Column obtained according to Experiment 4;
[0263] - Figure 4 4C: Flattened dome according to test 8
[0264] For a pipette of 30 μm diameter, the ratio of deposition area to the volume of ink to be deposited is higher. In order to allow a more rapid solidification of the nanoparticles and thus obtain a column with a constant diameter over its height, a solvent more volatile than DGME is required.
[0265] In trial 8, the withdrawal speed was too fast to form a column.
[0266] In Experiment 9, the column was able to be drawn out, but it was not possible to form a column of substantially constant diameter.
[0267] The posts were then cured on a hot plate at 150°C for 30 minutes.
[0268] Example 2: Silver Nanoparticles - Diluted Commercial Ink
[0269] The ink of Example 1 was diluted with a similar solvent, DGEE, to obtain a volume concentration of nanoparticles of 5 vol% (= 35 wt%).
[0270] Approach and contact were performed using a pipette having a tip diameter of either 1.5 μm or 8 μm as described in Example 1. The feedback control loop was not activated.
[0271] The results obtained are summarized in the following table:
[0272] [Table 2]
[0273] D = pipette diameter (μm)
[0274] Ve=withdrawal speed (μm / s)
[0275] Vr=fracture velocity (μm / s)
[0276] The more the ink is diluted, the greater the amount of liquid that is evaporated to obtain the solid phase of the nanoparticles, and the slower the withdrawal speed.
[0277] The posts were then cured on a hot plate at 150°C for 30 minutes.
[0278] Example 3: Silver Nanoparticles – Concentrated Commercial Ink
[0279] The ink of Example 1 was centrifuged at 7000 rpm for 30 minutes to remove the solvent DGME and increase the concentration of nanoparticles.
[0280] Glycerol was added as a second solvent to obtain the following formulation:
[0281] -Nanoparticles: 10% by volume;
[0282] - DGME: 65% by volume;
[0283] - Glycerol: 25% by volume.
[0284] Approach and contact were performed using a pipette having a tip diameter of either 1.5 μm or 8 μm as described in Example 1. The feedback control loop was disabled.
[0285] The results obtained are summarized in the following table:
[0286] [Table 3]
[0287] D = pipette diameter (μm)
[0288] Ve=withdrawal speed (μm / s)
[0289] Vr=fracture velocity (μm / s)
[0290] The ink is deposited and drawn off so that a column is formed without clogging the pipette. The low volatility of glycerol compensates for the increase in nanoparticle volume fraction.
[0291] The posts were then cured on a hot plate at 150°C for 30 minutes.
[0292] Example 4: Silver Nanoparticles – Commercial Ink
[0293] The ink used is commercial ink PVnanocell ref (Sycris TM P75DB-1), the composition of which as specified by the supplier includes:
[0294] -Silver nanoparticles (d50 = 70nm, d90 = 130nm, Determination), coated with a layer of polyvinyl pyrrolidone; its concentration is between 72 and 78% by weight, that is, about 10% by volume.
[0295] -Solvent DGBE.
[0296] Approach and contact were performed using a pipette having the tip diameter given in the table below as described in Example 1. The feedback control loop was deactivated.
[0297] The results obtained are summarized in the following table:
[0298] [Table 4]
[0299]
[0300] D = pipette diameter (μm)
[0301] Ve=withdrawal speed (μm / s)
[0302] Vr=fracture velocity (μm / s)
[0303] The solvent DGBE is less volatile than DGME; under the same temperature and atmospheric pressure conditions, DGBE evaporates more slowly than DGME, and therefore has a lower withdrawal rate.
[0304] The posts were then cured on a hot plate at 150°C for 30 minutes.
[0305] Comparative test 1:
[0306] The ink of Example 1 was centrifuged at 7000 rpm for 30 minutes to remove the solvent DGME and increase the concentration of nanoparticles.
[0307] -Nanoparticles: 16% by volume;
[0308] -DGME; 84% by volume;
[0309] As described in Example 1, the approach and contact were made using a pipette with a tip diameter of 8 μm. The pipette clogged too quickly and no column could be formed. No matter how quickly the pipette was withdrawn, only a few particles were deposited on the substrate (see Figure 5 ).
[0310] Example 5: Copper Nanoparticles - Diluted Commercial Ink
[0311] Commercial ink PVnanocell ref(Sycris TM IC50DM-7) The composition specified by the supplier includes:
[0312] - Copper nanoparticles (d50 = 50nm, d90 = 120nm, Determination), coated with a layer of polyvinyl pyrrolidone; its concentration is between 48% by weight and 52% by weight by mass, that is, about 9.8% by volume.
[0313] -Solvent DGME,
[0314] The commercial ink was diluted with DGME or DGEE and glycerol in a volume ratio of 70:15:15—ink:DGEE / DGM:glycerol, thereby obtaining a volume fraction of 6.5% by volume of copper nanoparticles.
[0315] Approach and contact were performed using a pipette having a tip diameter of 5 or 10 μm as described in Example 1. The feedback control loop was deactivated.
[0316] The posts were then cured on a hot plate at 150°C for 30 minutes under a nitrogen atmosphere.
[0317] The results obtained are summarized in the following table:
[0318] [Table 5]
[0319] D = pipette diameter (μm)
[0320] Ve=withdrawal speed (μm / s)
[0321] Vr=fracture velocity (μm / s)
[0322] Photos of the examples are provided at Figure 6 middle. Figure 6 6A in: D = 5 μm, Figure 6 6B in: D = 10 μm.
[0323] Example 6: Copper Nanoparticles - Diluted Commercial Ink
[0324] Commercial ink PVnanocell ref(Sycris TM IC50DM-7) The composition specified by the supplier includes:
[0325] - Copper nanoparticles (d50 = 50nm, d90 = 120nm, Determination), coated with a layer of polyvinyl pyrrolidone; its concentration is between 48% by weight and 52% by weight by mass, that is, about 9.8% by volume.
[0326] -Solvent DGME,
[0327] The commercial ink was diluted with DGME or DGEE and glycerol in a volume ratio of 50:40:10—ink:DGEE / DGME:glycerol, thereby obtaining a volume fraction of 4.9% by volume of copper nanoparticles.
[0328] Approach and contact were performed using a pipette having a tip diameter of 5 μm as described in Example 1. The feedback control loop was deactivated.
[0329] The posts were then cured on a hot plate at 150°C for 30 minutes under a nitrogen atmosphere.
[0330] The results obtained are summarized in the following table:
[0331] [Table 6]
[0332] Ve=withdrawal speed (μm / s)
[0333] Vr=fracture velocity (μm / s)
[0334] Figure 7 Photos corresponding to Experiment 32 are shown.
[0335] Comparative Example 2
[0336] The commercial ink PVnanocell ref (Sycris IC50DM-7) is composed of:
[0337] - Copper nanoparticles (d50 = 50nm, d90 = 120nm, Determination), coated with a layer of polyvinyl pyrrolidone; its concentration is between 48% by weight and 52% by weight by mass, that is, about 9.8% by volume.
[0338] -Solvent DGME,
[0339] The commercial ink was diluted with glycerol to a ratio of 50-50 by volume.
[0340] Thus, a copper nanoparticle volume fraction of 4.9% by volume was obtained.
[0341] Following the same procedure as before for forming columns, lines and dots of the ink containing nanoparticles were deposited using a 5 μm pipette (see Figure 8 8A, 8B), but even with a withdrawal speed as low as 0.01 μm / s, it is impossible to produce a column.
[0342] Here, the solvent is not volatile enough; even after complete evaporation of the DGME, sufficient glycerol remains to keep the ink liquid and prevent the nanoparticles from solidifying.
[0343] Example 7: Gold Nanoparticles – Commercial Ink
[0344] The laboratory created gold ink, which is composed of:
[0345] - Gold nanoparticles (d50=6 nm and d90=10 nm, measured by dynamic light scattering - DLS), coated with a layer of dispersant; its volume concentration is 0.4 vol%.
[0346] - ethanol, as component 1 of the first solvent, in an amount of 59.6% by volume,
[0347] - Water, as component 2 of the first solvent, in an amount of 30% by volume,
[0348] - Glycerol, as the second solvent, in an amount of 10% by volume,
[0349] The gold ink was injected into pipettes with a diameter of 1.5 or 8 μm following the procedure detailed in Example 1. The feedback control loop was deactivated. The break rate was 100 μm / s.
[0350] The posts were then cured on a hot plate at 200°C for 30 minutes.
[0351] The results obtained are summarized in the following table:
[0352] [Table 7]
[0353] D = pipette diameter (μm)
[0354] Ve=withdrawal speed (μm / s)
[0355] Fig. 9 Photos corresponding to Experiment 35 are shown.
[0356] Example 8: Variation of withdrawal speed as a function of pipette diameter
[0357] The ink of Example 1 was used to form columns by following the procedure guidelines detailed in Example 1. The maximum column formation rate without disrupting the meniscus as a function of the diameter of the pipette used is reported in Fig.10 The variation with the volume fraction of nanoparticles is reported in the graph of 10A in Fig.10 In the chart of 10B.
[0358] The diameter of the pipette was varied between 1 and 30 μm. It was observed that the more the diameter of the pipette increased, the more the withdrawal speed had to be reduced in order to form a column. Both the surface / volume ratio and the time necessary to evaporate the solvent increase with the size of the meniscus and therefore with the diameter of the pipette.
[0359] The volume fraction varies between 0 and 6 volume %. The higher the volume fraction occupied by nanoparticles, the faster the withdrawal speed is in order to form a column. When the volume fraction of nanoparticles increases, the amount of solvent to be evaporated is smaller; solidification of the ink in the meniscus is achieved faster.
[0360] Example 9: Wires connected to the pillars, made of silver or copper
[0361] The ink of Example 4 (for silver) and the ink of Example 6 (for copper) were used to deposit the conductive lines and then the pillars; Runs 36 and 37, respectively.
[0362] As described in Example 1, the approach and contact are made using a pipette, the tip diameter of which is 5 μm. Once the pipette is in contact, the PLL loop remains active so as to keep the pipette close to the surface and thus avoid the meniscus from breaking. The substrate is moved horizontally at a speed of 1 to 1000 μm / s so that the ink drawn through the pipette is deposited on the substrate along the path. Once the nanoparticle line is formed, the pipette is kept in contact and stationary for 1 to 30 seconds, and then the substrate is withdrawn from the pipette as described in Example 1 (the feedback control loop is deactivated). A column is thus obtained.
[0363] The posts were then cured on a hot plate at 150°C for 30 minutes (under nitrogen atmosphere for copper).
[0364] The results obtained are summarized in the following table:
[0365] [Table 8]
[0366] Ve=withdrawal speed (μm / s)
[0367] Vr=fracture velocity (μm / s)
[0368] Fig.11 Photos corresponding to Experiment 37 are shown.
[0369] Example 10: Silver Nanoparticles – Commercial Ink
[0370] The ink of Example 1 was used in this example.
[0371] It was injected into a pipette with a diameter of 4 μm following the procedure detailed in Example 1. The feedback control loop was activated. The breaking speed was 100 μm / s.
[0372] The posts were then cured on a hot plate at 200°C for 30 minutes.
[0373] A column with a diameter of 4 μm and a height of 280 μm (aspect ratio of 70) was obtained. The SEM image of this column is shown in Fig.12 middle.
Claims
1. A method for manufacturing a three-dimensional nanostructure, the method comprising the following steps: - oscillating an injector (100) between a low position in contact with the substrate (20) and a high position out of contact with the substrate (20), the injector (100) comprising an injection hole (108) having a diameter greater than 0.1 μm; - during the period when the ejection hole (108) of the ejector (100) is in contact with the substrate (20), an ink is deposited on the substrate (20) by the ejector, the ink comprising, in volume % relative to the total volume of the ink: - less than 15% of nanoparticles selected from metal nanoparticles, metal oxide nanoparticles, graphene oxide nanoparticles, quantum dots, or a combination thereof; -0.5% to 5% dispersant, - at least 80% of a solvent capable of dispersing the metal nanoparticles to form the ink to be jetted and having sufficient volatility to allow the ink to solidify once deposited; and - withdrawing the ejector (100) from the substrate (20) in a direction substantially perpendicular to the substrate at a speed less than or equal to 10 μm / s while maintaining a flow of ink exiting from the ejector.
2. The method according to the preceding claim, wherein the ink comprises from 0.05% to 15% by volume, advantageously from 0.2% to 10% by volume and more advantageously from 4 to 8% by volume of nanoparticles relative to the total volume of the ink.
3. The method according to any of the preceding claims, wherein the diameter of the injection hole (108) is 0.1 μm to 50 μm, advantageously 0.5 μm to 30 μm.
4. The method according to any one of the preceding claims, wherein the volatile solvent comprises a solvent selected from the group consisting of water, alcohols, glycols, glycol ethers and mixtures thereof.
5. Method according to the preceding claim, wherein the ink comprises 80% to 99.45% by volume of the solvent relative to the total volume of the ink.
6. The method according to any one of claims 4 or 5, wherein the volatile solvent further comprises a second solvent, which is glycerol, in an amount advantageously such that the ink comprises 0% to 25% by volume of glycerol relative to the total volume of the ink.
7. The method according to any one of the preceding claims, wherein the metal of the metal nanoparticles is selected from the group consisting of silver, copper, gold, platinum, nickel, aluminum, cobalt, zinc, indium, palladium and combinations or alloys thereof.
8. The method according to any one of claims 1 to 7, wherein the metal oxide of the metal oxide nanoparticles is selected from ZnO, TiO2, ITO (indium tin oxide) or V2O5.
9. The method according to any one of the preceding claims, wherein the ink further comprises a dispersant, which is advantageously selected from: polyvinyl pyrrolidone (PVP), gum arabic, polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyallylamine (PAAm), sodium polystyrene sulfonate (PSS), 3-(aminopropyl)trimethylsilane (APS), fatty acids, cetyltrimethylammonium bromide (CTAB), tetraoctylammonium bromide (TOAB), sodium citrate, laurylamine, dodecanethiol, mercapto-polyethylene glycol, mercapto-polypropylene glycol, or a combination thereof.
10. The method according to any of the preceding claims, wherein during the step of withdrawing the ejector from the substrate, the ejector is withdrawn at a speed of 1 μm / s to 10 μm / s.
11. Method according to any of the preceding claims, comprising the step of breaking the three-dimensional nanostructure formed and the ink to be deposited, advantageously by withdrawing the ejector (100) from the substrate (20) at a speed greater than 10 μm / s.
12. The method according to any one of the preceding claims, further comprising performing at least one cycle of the following steps to form at least one second three-dimensional nanostructure: - moving the injector relative to the substrate (20) in a direction (x, y) parallel to the substrate, and - Perform the steps according to any one of claims 1 to 11.
13. A method according to any one of the preceding claims, comprising the step of curing the substrate containing the formed nanostructures.
14. A product comprising a substrate on which is deposited at least one three-dimensional nanostructure obtained by the method according to any one of the preceding claims, wherein the nanostructure is in the form of a tapered pin having a diameter that decreases in an upward direction and having at least one of the following characteristics: - the diameter of the substrate varies between 0.5 μm and 50 μm; - The diameter of the apex varies between 0.2 μm and 30 μm; - The slope angle varies from 0.1° to 70° relative to the vertical.
15. A product comprising a substrate on which is deposited at least one three-dimensional nanostructure obtained by the method according to any one of claims 1 to 13, wherein the nanostructure is in the form of a pillar whose height is at least fifteen times the diameter of the substrate, the diameter of the substrate being advantageously less than 1 μm.
Citation Information
Patent Citations
Luminescent, cadmium-free core / multi-shell quantum dots on the basis of indium phosphide
EP2820108A1
Stable dispersions of monocrystalline nanometric silver particles
WO2012078590A2
System for controlled depositing of a fluid on a substrate
WO2020128310A1
Quantum dot with a core-shell structure, method of preparing them and electronic device
WO2023274486A1